Fish powder: Assessing profitability and affordability in Timor-Leste - Ximenes, Imanuel; Bonis-Profumo, Gianna; Simões, Noviana; Duarte, Agustinha; Pinto, Abelita; Hunnam, Kimberley (Pacific Community (SPC), 2025)
This study investigates the financial profitability of small scale, home-based fish powder production in Timor-Leste, by estimating the costs and potential profits of producing one kilogram of product using one particular recipe. It also estimates affordability for schools, based on existing allocated school meal budgets. By providing insights into these aspects, this study seeks to identify research gaps and inform decision making and investment that can achieve both nutrition and livelihood objectives in rural and coastal Timor-Leste.